SmgGDS: An Emerging Master Regulator of Prenylation and Trafficking by Small GTPases in the Ras and Rho Families - Brandt, Anthony C.; Koehn, Olivia J.; Williams, Carol L. (Frontiers in Molecular Biosciences, 2021)
Small GTPases in the Ras and Rho families are major signaling proteins that traffic throughout the cell and are activated by guanine nucleotide exchange factors (GEFs). Understanding how these events are regulated will help define new therapeutic strategies for cancer and other disorders involving abnormal signaling by these small GTPases. Newly synthesized small GTPases are prenylated by cytosolic prenyltransferases (PTases) and undergo post-prenylation processing at the endoplasmic reticulum (ER). The prenylated GTPase interacts with a chaperone that escorts it to membranes, the nucleus, and other sites. A growing body of evidence indicates that SmgGDS-607 and SmgGDS-558, which are splice variants of SmgGDS (gene name RAP1GDS1), are major regulators of the prenylation, post-prenylation processing, and trafficking of Ras and Rho family members. SmgGDS-607 binds pre-prenylated Ras and Rho family members, while SmgGDS-558 binds the prenylated form of these GTPases. This review discusses the history of SmgGDS research and explains our current understanding of how SmgGDS splice variants regulate the prenylation and trafficking of small GTPases. We present a new model proposing that poorly defined GEFs and GDI displacement factors (GDFs) induce SmgGDS-607 to release pre-prenylated GTPases to the PTase or release pre-prenylated GTPases in the nucleus. GEFs and GDFs might also induce SmgGDS-558 to release prenylated GTPases to the ER membrane for post-prenylation processing, or release prenylated GTPases at the plasma membrane or in the nucleus. We discuss evidence that mutant forms of RabL3 and Rab22a might serve as GDFs for SmgGDS, and review the inhibitory actions of DiRas1, which competitively blocks the binding of other small GTPases to SmgGDS. We conclude with a discussion of promising new strategies for therapeutic targeting of SmgGDS in cancer, involving splice-switching oligonucleotides and peptide inhibitors.